2005
DOI: 10.1111/j.1467-6486.2005.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Profit Sharing on the Performance of Financial Services Firms*

Abstract: Relying on macro theories (agency and organizational control) as well as micro theories (goal setting and expectancy), this study investigates the impact of profit-sharing plan (PSP) adoption on the value creation process of financial services firms. The study relies on a comprehensive methodological approach that is both quantitative, with a dual cross-sectional/longitudinal (pre-post) design that compares PSP adopters with a control group of PSP non-adopter firms, and qualitative through interviews with some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 73 publications
3
32
0
1
Order By: Relevance
“…Magnan and St-Onge (2005) confirm that prediction for firms adopting PSPs. However, it is not clear from their findings if the enhancement in profitability results from a one-time earnings improvement or from continuous earnings growth.…”
Section: Conceptual Framework and Hypothesessupporting
confidence: 78%
“…Magnan and St-Onge (2005) confirm that prediction for firms adopting PSPs. However, it is not clear from their findings if the enhancement in profitability results from a one-time earnings improvement or from continuous earnings growth.…”
Section: Conceptual Framework and Hypothesessupporting
confidence: 78%
“…However, while the research evidence is quite clear that employee profit sharing does increase company productivity on average (Weitzman and Kruse 1990;Blasi, Freeman, Mackin and Kruse 2010), the evidence is equally clear that it does not do so in all cases (Kruse 1993;Magnan and St-Onge 2005;Robinson and Wilson 2006). But note that a causal connection between employee profit sharing and employer productivity is not a necessary condition for profit sharing to result in an increase in employee earnings.…”
Section: Theoretical and Empirical Backgroundmentioning
confidence: 85%
“…Profit sharing relies on the output of a collective of individuals who will later share the fruit of their commonly created productivity. This is likely to foster greater relatedness, even if it could potentially decrease feelings of competence (because such systems are known to lack a clear link between individual performance and firm productivity; Magnan & St-Onge, 2005). Two studies found that rewards in the form of profit sharing and stock ownership were positively related to affective organizational commitment (Coyle-Shapiro, Morrow, Richardson, & Dunn, 2002;Kuvaas, 2003), which has been linked to autonomous motivation (Gagne´, Boies, Martens, & Donia, 2006).…”
Section: Objectivity Of the Performance Appraisal Methodsmentioning
confidence: 99%